2022
DOI: 10.1167/iovs.63.11.8
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Expression of Retinoschisin by Retinal Bipolar Cells in XLRS Promotes Resolution of Retinoschisis Cysts Sans RS1 From Photoreceptors

Abstract: Purpose Loss of retinoschisin (RS1) function underlies X-linked retinoschisis (XLRS) pathology. In the retina, both photoreceptor inner segments and bipolar cells express RS1. However, the loss of RS1 function causes schisis primarily in the inner retina. To understand these cell type–specific phenotypes, we decoupled RS1 effects in bipolar cells from that in photoreceptors. Methods Bipolar cell transgene RS1 expression was achieved using two inner retina–specific promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…However, our study demonstrated that photoreceptor cells were developmentally delayed at RS1 mutation ROs. Besides the photoreceptor cells, we also identified Müller glial cells and bipolar cells, which are considered to be related to XLRS [54][55][56]. However, the number of Müller glial cells and bipolar cells did not differ significantly between patient and control ROs at day 260.…”
Section: Discussionmentioning
confidence: 77%
“…However, our study demonstrated that photoreceptor cells were developmentally delayed at RS1 mutation ROs. Besides the photoreceptor cells, we also identified Müller glial cells and bipolar cells, which are considered to be related to XLRS [54][55][56]. However, the number of Müller glial cells and bipolar cells did not differ significantly between patient and control ROs at day 260.…”
Section: Discussionmentioning
confidence: 77%
“…It is predominantly expressed in the inner photoreceptors and bipolar cells [4]. There are reports supporting that RS1 expression is significantly lower in retinoschisis patients [5] and that RS1 gene therapy is effective in resolving retinoschisis in RS1-knockout mice [6,7]. RS1 plays an important role in maintaining an anatomically normal and functional macula.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, the protein is first observed around postnatal day six (P6), and adult expression patterning is reached at P12 [18]. In the mature retina only PRs and bipolar cells are involved in RS1 synthesis, subsequently, in its secretion [18,33,34]. As a consequence, RS1 is detected throughout the inner and outer mature retina as a secreted protein ( [18,35].…”
Section: Localizationmentioning
confidence: 99%
“…Gene delivery for treating XLRS should be focused on the outer retina, specifically the photoreceptors, and in the inner retina targeting bipolar cells, since they are involved in RS1 synthesis in the mature retina [18,33,34]. Transduction of RS1 in photoreceptors of a Rs1h-deficient mouse model showed significant improvements in RS1 production and secretion and a reduced the number of cavities, improved retinal organization and led to functional rescue [54].…”
Section: Adeno-associated Viral Vector-mediated Gene Augmentation The...mentioning
confidence: 99%
See 1 more Smart Citation